Bioethics fundamental principles - Gómez Sánchez, Pío (2015)
Background. It is considered that the concept of bioethics is born in Seattle early in the sixties when a non-medical committee was created to decide who had preference for hemodialysis. Term bioethics is given by the North American oncologist Potter in 1970. In 1974 the USA Congress creates a commission to elaborate ethical directives and protect rights of persons participating in research studies. Belmont´s report appears in 1978, one of the first documents written on bioethics, where autonomy, beneficent professional practice and justice are recognized. In 1979 Beauchamp and Childress introduce the concept of non-maleficency.Principles of bioethics. Principle of autonomy: is the obligation to observe each individual’s values and personal options in such basic decisions concerned. Principle of beneficence: is the obligation to do well.Principle of non-maleficence: is respect to the human being integrity, ever more relevant with technical and scientific advances. Principle of justice: is the equitable division of charges and benefits in vital wellbeing, avoiding access discrimination to sanitary resources. Role of gynecologists and obstetricians. To try equitable access to health services by women independently from age, race, marital, socioeconomical or religious status, recognizing sexual and reproductive rights an integral part of human rights.